India's coverage in COMPENDEX plus in 1990 and 1994 an analysis - Rao Ravichandra I K; Suma P (Bangalore ISI, 1997)
This technical report discusses the results of the study on Indiats coverage in COMPENDEX Plus bibliographic database in 1990 and 1994. Type of documents, language journals used by the Indian engineering & technocrats and individual institutional players
Technical Report
Keywords: India; Science-research; Scientific literatures